Integration of Information, Communication and Technology in Secondary Schools of Nepal: Policies and Practices - Ojha, Lok Raj (A Bi-annual South Asian Journal of Research & Innovation, 2023)
The article explores the policies, provisions, and practices on the integration of ICT in the education system of Nepal. It was a quantitative survey study in which the policy provisions and practices were analyzed critically and empirically. The participants were selected using purposive and convenience sampling from the targeted population. An online questionnaire with 29 items was constructed as a tool for data collection and was distributed to secondary-level teachers, who were teaching at government public schools in Nepal via emails. The data was further analyzed statistically by calculating Percentage, Average, Chi-Square test (Goodness of fit), and P-value analysis using MS Excel. A value of p<0.05 was considered significant. It was found that integration of ICT in education is positioned as a major concerning phenomenon in educational policies and programs conducted by the Government of Nepal. Secondary schools in Nepal are still facing numerous deficiencies and challenges, among them the scarcity of technical knowledge and competency of teachers is a major one. Based on UNESCO’s four-stage continuum (emerging phase, applying phase, infusing phase, and transforming phase); public schools in Nepal are in the emerging phase as the development of ICT-related infrastructure, nevertheless, only a few numbers of schools have competent, dedicated, qualified, and trained human resources. Therefore, Governmental and nongovernmental organizations and policymakers have clear action plans to build infrastructures, teacher motivation, skill, competence, and positive attitudes of teachers, parents, and students.